Understanding the experiences and needs of individuals with Spinal Muscular Atrophy and their parents: a qualitative study. Issue 1 (December 2015) - Qian, Ying; McGraw, Sarah; Henne, Jeff; Jarecki, Jill; Hobby, Kenneth; Yeh, Wei-Shi
Abstract Background The clinical features of SMA, which range along a spectrum of severity, are relatively well described. In contrast, the literature on how individuals with SMA and their families experience this condition is limited. To address this gap, we undertook a qualitative study with individuals affected by SMA Types I, II and III, parents of those affected, and clinicians. Methods We completed 16 focus group sessions and 37 interviews in the US with 96 participants including: 21 with individuals with SMA; 64 parents of individuals affected by SMA; and 11 clinicians who specialize in the care of SMA patients. Results The Diagnostic Journey : Families reported substantial diagnostic delays owing to: 1) lack of awareness and knowledge about SMA; 2) the difficulty of distinguishing normal from abnormal development; and 3) the challenge of differential diagnosis. Lack of sensitivity in how clinicians communicated this potentially devastating diagnosis compounded parents' negative impressions. Newborn Screening : Parents generally held positive views about adding SMA to newborn screening panels. For example, it would: 1) enable earlier access to care; 2) shorten the diagnostic journey; and 3) give families more time to prepare to care for a disabled child. Some noted negative outcomes such as prematurely affecting a parent's relationship with a child before symptoms are evident. The Psychosocial Impact of Living with SMA : Ten thematic areas characterized the impact: 1) confronting premature death; 2) making difficult treatment choices; 3) fearing the loss of functional ability; 4) coming to terms with lost expectations; 5) loss of sleep and stress; 6) stigma; 7) limitations on social activities; 8) independence; 9) uncertainty and helplessness; and 10) family finances. Conclusions The results of this study suggest high levels of burden experienced by individuals with SMA and their families. The difficulties of living with SMA begin with the long and often arduous process of finding a diagnosis for their child. Newborn screening for SMA is seen as an important step toward shortening this journey. The psychosocial effects of coping with SMA are substantial and wide ranging both for the individual living with this condition and family members of affected individuals.